Oviposition activity of Haemagogus leucocelaenus (Diptera: Culicidae) during the rainy and dry seasons, in areas with yellow fever virus circulation in the Atlantic Forest, Rio de Janeiro, Brazil. - Jeronimo Alencar; Cecilia Ferreira de Mello; Paulo José Leite; Amanda Queiroz Bastos; Shayenne Olsson Freitas Silva; Michele Serdeiro; Júlia Dos Santos Silva; Gerson Azulim Müller (PLoS ONE)
The present study aims to analyze the effectiveness of ovitraps in the capture of Hg leucocelaenus eggs and evaluate the influence of the dry and rainy seasons on their abundance and hatching rates. The eggs were collected in the Atlantic Forest of State of Rio de Janeiro, Brazil, an area in which the yellow fever virus is known to circulate. We distributed 15 ovitraps in three sampling points, with five ovitraps per point. We distributed 15 ovitraps in three sampling points on trees within a forested area, which were sequentially numbered, monitored, and replaced every two weeks from October 2016 to April 2018. There was a high dominance of Hg. leucocelaenus eggs (98.4%) and a variation in egg hatching rates between the wet and dry seasons. These rates were 1.5 times higher in the rainy season than in the dry season. The rainy season also showed a greater abundance of eggs and higher values of ovitrap positivity and egg density indexes in the installed ovitraps. The abundances of Hg. leucocelaenus eggs were positively correlated with mean monthly temperature and air humidity but not significantly correlated with accumulated precipitation. These results, as well as their implications for the possible use of ovitraps to monitor vector mosquitoes of yellow fever in the study region, are discussed.